Juridical Analysis of Court Decisions Regarding Civil Lawsuits from a Civil Law Perspective - Danialsyah (Inovasi Pratama Internasional. Ltd, 2024)
The role of the head of the district court is to review and consider all requests for enforcement in their court in order to prevent any impediments to the enforcement of court decisions that have already attained permanent legal status. Thus, the objective of this paper is to identify the factors that impede the execution of court decisions with lasting legal effect. The research utilized the descriptive-analytical approach with a normative juridical emphasis. The study revealed that the primary reasons for delayed execution of court decisions with permanent legal force were due to limited availability of executors, budget constraints, opposition by third parties, and judicial review of decisions.<< To overcome the challenges encountered in executing judicial decisions by the Supreme Court of the Republic of Indonesia, it is crucial to train State Civil Servants who are specialized in carrying out their functions effectively through education that is tailored to their role.